PERBEDAAN KEMAMPUAN BERBAHASA ANAK USIA 5-6 TAHUN MELALUI BUKU CERITA DIGITAL DI TK AISYIYAH BUSTHANUL ATHFAL 06 MEDAN - Delta Fariza; Wan Nova Listia (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2025)
This study aims to determine the difference in language skills in children aged 5-6 years through the use of digital storybooks at Aisyiyah Busthanul Athfal 06 Medan Kindergarten. The approach used was experimental research with a one group pretest-posttest design. The sample in this study amounted to 15 children selected using purposive sampling technique. Data collection instruments include observation and documentation guidelines. Data analysis was carried out using non-parametric statistical tests, namely the Wilcoxon Signed-Rank Test. The results showed that there were significant differences in children's language skills, especially in the aspects of listening and speaking, before and after treatment. This is indicated by an increase in the average score from 4.13 in the pretest to 7.47 in the posttest. The significance value obtained is 0.001 <0.05, so H₀ is rejected and Hₐ is accepted. Thus, it can be concluded that the use of digital storybooks has an effect on improving the language skills of children aged 5-6 years at Aisyiyah Busthanul Athfal 06 Medan Kindergarten.